Access to Justice: Addressing Case Backlogs and Promoting Gender-Sensitive Alternative Dispute Resolution - Khurshid Rajib (Mimbar Keadilan, 2025)
Access to justice is a fundamental element in ensuring human rights and the rule of law. In Bangladesh, the judicial system faces serious challenges, most notably the issue of case backlogs that hinder the timely, fair, and efficient resolution of disputes. This study aims to analyze the root causes of the legal system’s congestion and to explore the potential of gender-sensitive ADR mechanisms as a means to broaden access to justice, particularly for vulnerable groups such as women. Using a descriptive qualitative approach, this study relies on secondary data from policy reports, academic publications, and relevant field studies. The findings indicate that the formal judicial system in Bangladesh is burdened by a lack of human resources and infrastructure, as well as by complex and gender-insensitive legal procedures. In contrast, ADR mechanisms such as mediation and arbitration hold significant promise for reducing the caseload of the courts and enabling more participatory and expedited dispute resolution processes. However, the effective implementation of ADR continues to face structural challenges, including gender bias, limited public awareness, and the need for institutional reform and gender-based training. Therefore, a multi-level approach that includes policy reform, gender-sensitive capacity building, and community advocacy is essential to promote a more responsive and inclusive legal system in Bangladesh.